Factors influencing survival after hepatectomy for metastases from gastric cancer. Issue 8 (August 2016) - Tiberio, G.A.M.; Ministrini, S.; Gardini, A.; Marrelli, D.; Marchet, A.; Cipollari, C.; Graziosi, L.; Pedrazzani, C.; Baiocchi, G.L.; La Barba, G.; Roviello, F.; Donini, A.; et al.
Abstract: Purpose: To investigate clinical factors influencing the prognosis of patients submitted to hepatectomy for metastases from gastric cancer and their clinical role. Methods: Retrospective multi-center chart review. We evaluated how survival from surgery was influenced by patient-related, gastric cancer-related, metastasis-related and treatment-related candidate prognostic factors. Results: One hundred and five patients submitted to hepatectomy for metastases from gastric cancer, in the synchronous and metachronous setting of the disease. In 89 cases a R0 resection was achieved, while in 16 a R+ hepatic resection was performed. Adjuvant chemotherapy was administered to 29 patients. Surgical mortality was 1% and morbidity 13.3%. Median disease-free survival was 10 months, median overall survival was 14.6 months. Overall 1, 3, and 5-year survival rates were 58.2%, 20.3%, and 13.1%, respectively. Survival was influenced independently by the factor T of the gastric primary (p < 0.001), by the curativity of surgical procedure (p = 0.001), by the timing of hepatic involvement (p < 0.001) and by adjuvant chemotherapy (p < 0.001). T4 gastric cancer, R+ resection, synchronous metastases, and abstention from adjuvant chemotherapy were associated with a worse prognosis; T4 gastric cancer and R+ resections displayed a cumulative effect (p < 0.001). Conclusions: Our data show that R0 resection must be pursued whenever possible. Furthermore, in the synchronous setting, the coexistence of T4 gastric primaries and R+ resections suggests prudence and probably abstention from hepatectomy. Finally, a multimodal treatment associating surgery and chemotherapy offers the best survival results.